Analysis of Cohesion and Coherence in the Background of Thesis Written by English Education Study Program Students of IAIN Bengkulu in Period September 2020 - Pebri Prandika Putra; Yuni Astari (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2022)
This study aimed to find kinds of cohesion and coherence in the background section of thesis, it also focused to analyze the use of cohesion and coherence in the background section of thesis by English Education Study Program students of IAIN Bengkulu in period September 2020. This study concerned with text analysis. the method in this study was descriptive qualitative. The writer used documentation in collecting data. The data of this study were ten background of thesis which were taken randomly from the background section of thesis by English Education Study Program students of IAIN Bengkulu in period September 2020. The findings of the study showed cohesion and coherence in the background of thesis achieve by the used cohesive and coherent devices. There are two types of cohesion, namely grammatical cohesion and lexical cohesion. From the findings, the students can build grammatical cohesion which consist of reference as much as 53%, substitution 6%, and conjunction 35%. Unfortunately, ellipsis is not found in the background of thesis. While lexical cohesion which consist of reiteration as much as 4% and 2%. In addition, students build coherence as much as 57% at consistent pronoun, 38% at transition signals, 3% at repeating key nouns, and 2% at logical order. In conclusion, the writer concluded that the background section of thesis by English Education Study Program students of IAIN Bengkulu in period September 2020 are organized as well and become good background of thesis because used cohesion and coherence devices in creating the sentences and paragraphs variously.